(untitled) (Research, Society and Development, 2022)
Cervical cancer is responsible for about 265,000 deaths a year worldwide, being the fourth most frequent cause of cancer death in women, with approximately 530,000 new cases per year. The performance of the cytopathological examination and the aspects that involve its quality are fundamental in the screening of cervical cancer. Despite having a slow evolution, cervical cancer is characterized as an important public health problem worldwide, due to the high incidence and mortality rates in the female population. The nurse works through available approaches in the health area, articulating them for the prevention and/or health promotion, combining assistance with knowledge about risk factors for cervical cancer. Early detection is the most indicated due to the effectiveness in reducing cases of cervical cancer, configured through screening programs and actions. The study aimed to reveal the practice of nurses from the Family Health Strategies in screening for cervical cancer in Primary Health Care in a municipality in the interior of Minas Gerais. Thirty-three nurses working in Primary Health Care participated in the study, and the focus group technique was used to collect data, through a digital videoconferencing platform, due to the COVID-19 pandemic, enabling distance meetings. Data analysis was performed using Content Analysis, according to Bardin, and Atlas ti software, version 8, was used to organize the speeches, after transcribing the audios in full. There were suggestions and testimonials about the obstacles faced in the nurses’ work process and raising important points that could be changed, for improvements in the quality of care and nurses’ performance in the Health Units.